Acuchimay: pre-hispanic settlement from the Warpa and Wari period in the Ayacucho basin - Carhuas Tenorio, Héctor (2021)
Part of a research work that involves the archeology of the south-central Sierra of the Andean territory is presented, corresponding to the chronological framework of the Early Intermediate Period and the Middle Horizon. Acuchimay is one of the pre-Hispanic settlements adjacent to the archaeological site of Rudaqasa, located in the heart of the current city of Ayacucho, which keeps the testimony of an ancient occupation of the Warpa and Wari times, as well as other sites, located throughout the Huarpa river basin. The fundamental objective is to know and retrieve all the possible existing information to define the importance of the site during the Warpa and Wari times. The method used is descriptive and synthesized from the visit around Acuchimay and the cultural material recovered from the surface; likewise, it is complemented by some private collections existing in the properties of the modern population of the site. Based on the archaeological evidence, we reached a general vision about the characteristic of the site to understand what the sociocultural dynamics was in the ancient Ayacucho basin.